Squamous cell carcinoma: 2021 updated review of treatment. Issue 4 (17th January 2022) - Dreyfuss, Isabella; Kamath, Preetha; Frech, Fabio; Hernandez, Loren; Nouri, Keyvan
Abstract: Squamous cell carcinoma is the second most common cutaneous malignancy, requiring early diagnosis to prevent metastasis. Updated guidelines in the definition of clinical features, diagnostic modalities, grading, staging, surgical, and nonsurgical treatment methods are necessary. Diagnostic methods from biopsy, dermoscopy, and reflectance confocal microscopy have improved to include high‐frequency ultrasonography, optical coherence tomography, and computed tomography. Non‐surgical treatment methods include topical therapy, cryosurgery, photodynamic therapy, and radiation. Surgical treatment methods include surgical excision with margins and Mohs surgery. Clinical trials encourage further research to address the knowledge base of genetic variations and lymph node metastasis.